Analysis of Persepolis Marjane Satrapi as an unusual chronicle due to the form of the graphic novel - Kisztelińska-Węgrzyńska, Agnieszka; Krauze, Maciej; Agnieszka Gralak (Jednostka wobec globalnego wymiaru stosunków międzynarodowych, 2021)
In this article, instead of referring directly to the problem of the individual as a subject in international relations, I will focus on finding a way to write about it. I’m interested in how to define a convenient narrative. Whether to focus on the individual perspective of the individual, or maybe try to take one side of the relationship or rather include a bilateral perspective. I assume that properly codified content must be accompanied by a new form. In search of unusual texts with given determinants, I intend to analyze the graphic novel Persepolis Marjane Satrapi. I will also use the neo-formal method of textual analysis, which I learned at cultural studies and historical method, thus combining two disciplines of the humanities. In the thought that art can be a universal language and creative expression a means of communication.